2021
DOI: 10.15406/ijvv.2021.06.00110
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the Congolese population on Covid-19 vaccination: cross-sectional survey of online

Abstract: COVID-19 vaccines will become available in Democratic Republic of Congo soon. Understanding communities’ responses to the forthcoming COVID-19 vaccines is important. We was conducted an analytical cross-sectional study online in 26 provinces of the Democratic Republic of Congo during the period from January to March 2021. A total of 11971 responses were included; mean age of respondents was 35.1±10.4 years; 79.4% were males; 90.5% had university school education and 55.4% has a high socioeconomic level. A freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Two of the 18 studies reported a positive perception [34,46] of the vaccine, while five of the 18 studies reported an overall negative perception [26,30,48,53,56] of the vaccine. According to the findings, two studies were diametrically opposed regarding attitudes and perceptions toward the vaccine.…”
Section: Attitudes and Perceptions Regarding Covid-19 Vaccines Among ...mentioning
confidence: 98%
See 2 more Smart Citations
“…Two of the 18 studies reported a positive perception [34,46] of the vaccine, while five of the 18 studies reported an overall negative perception [26,30,48,53,56] of the vaccine. According to the findings, two studies were diametrically opposed regarding attitudes and perceptions toward the vaccine.…”
Section: Attitudes and Perceptions Regarding Covid-19 Vaccines Among ...mentioning
confidence: 98%
“…Thirty-three studies (n = 33) highlighted the barriers associated with COVID-19 vaccine uptake. Of those twenty-nine studies (n = 29) cited fears over potential side effects and the newly developed vaccine being unsafe for the African population [27,29,30,[32][33][34][35][36][37][40][41][42][43][44][45]48,50,[54][55][56][57][58][59][60][61][62][63][64].…”
Section: Barriers To the Uptake Of The Covid-19 Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of Covid-19 vaccination program in its first year has not been well described in previous studies. Research conducted where either limited in scope like addressing one province [19,20] or one component of the vaccination for instance, the communication, the demand generation [21][22][23][24]. The only study that gave an overview of implementation was a commentary but was limited as it only focused on ChAdOx1 [25].…”
Section: Introductionmentioning
confidence: 99%